Seroepidemiology of SARS-CoV-2 infections in an urban population-based cohort in León, Nicaragua. (20th October 2021) - González, Fredman; Vielot, Nadja A.; Sciaudone, Michael; Toval-Ruíz, Christian; Premkumar, Lakshmanane; Gutierrez, Lester; Cuadra, Edwing Centeno; Munguia, Nancy; Blandón, Patricia; de Silva, Aravinda M.; Rubinstein, Rebecca; Bowman, Natalie; et al.
Abstract: In a Nicaraguan population-based cohort, SARS-CoV-2 seroprevalence reached 28% in the first 6 months of the country's epidemic and reached 35% 6 months later. Immune waning was uncommon. Individuals with a seropositive household member were over three times as likely to be seropositive themselves, suggesting the importance of household transmission.